Valorization of Rosehip (Rosa canina L.) Pomace Using Unconventional Carbohydrate Carriers for Beverage Obtainment - Anna Michalska-Ciechanowska; Jessica Brzezowska; Nancy Nicolet; Kamil Haładyn; Wolfram Manuel Brück; Aleksandra Hendrysiak; Wilfried Andlauer (Molecules)
Rosehip is of notable scientific interest due to its rich content of bioactives and its wide-ranging applications in nutrition, cosmetics and pharmaceuticals. The valorization of rosehip by-products, such as pomace, is highly significant for promoting sustainability. This study investigates the development of rosehip-based powders and beverage prototypes derived from both juice and pomace to evaluate the potential use of pomace in instant beverage design and compare it with juice-based formulations. Three matrices were evaluated: non-pasteurized and pasteurized juice, as well as non-pasteurized pomace preparations. Powders were produced by freeze- and spray drying using maltodextrin, inulin and unconventional carriers, i.e., palatinose and trehalose. The results demonstrated that carrier addition significantly influenced the physical and techno-functional properties of the powders, such as moisture content (below 10%), water activity (below 0.35), solubility (above 85%), and color indexes (yellowness and browning). The water absorption capacity varied with drying techniques, particularly for inulin-enriched samples, while the matrix type affected the ascorbic acid content. Non-pasteurized pomace powders exhibited a higher antioxidant capacity (67.7 mmol Trolox/100 g dry matter) than their juice counterparts (52.2 mmol Trolox/100 g dry matter), highlighting the potential of the pomace matrix for beverage production. Because of their favorable properties, spray-dried samples were also selected for reconstitution into prototype beverages, among which those obtained from pomace showed a higher antioxidant potential. An analysis of particle sizes, which ranged between 34 nm and 7363 nm, revealed potential interactions between the carrier and matrix, reflected in the distinct behavior of carrier-only samples. Both the carrier type and the matrix significantly contributed to the final properties of the beverages, providing valuable insights for the design of functional food products.